2019
DOI: 10.7567/1347-4065/ab1644
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of wall propagation and surface reflection effects on ultrasound fields generated inside a small container

Abstract: In studies on the bioeffects of ultrasound exposure on cells cultured in a Petri dish, an understanding of the pressure field generated inside the dish is essential to achieve better dosimetry of ultrasound exposure. In this study, ultrasound fields generated inside four types of small containers designed to mimic a Petri dish were visualized using the focused shadowgraphy technique. The results revealed that wall propagation and water surface reflection of ultrasound make a complex standing wave field in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In the case that a plane wave incidents into a flat water surface perpendicularly, the reflected wave is also a plane wave, and therefore, the standing wave created by the interference of the two waves is also a plane shape. When perfect reflection occurs at the water surface, the pressure amplitude of the standing wave is doubled, and our previous visualization experiments 28) confirmed that the brightness of the visualized image also increases to the same level.…”
Section: Effects Of Water Surface Shape On the Cavitation Threshold A...supporting
confidence: 63%
See 1 more Smart Citation
“…In the case that a plane wave incidents into a flat water surface perpendicularly, the reflected wave is also a plane wave, and therefore, the standing wave created by the interference of the two waves is also a plane shape. When perfect reflection occurs at the water surface, the pressure amplitude of the standing wave is doubled, and our previous visualization experiments 28) confirmed that the brightness of the visualized image also increases to the same level.…”
Section: Effects Of Water Surface Shape On the Cavitation Threshold A...supporting
confidence: 63%
“…The technique is useful for visualizing nodes and antinodes of an ultrasound standing wave field from a set of instantaneous field images. 28) The bright lines (high-pressure regions) appear at half-wavelength intervals (white arrows), indicating the occurrence of a standing wave field. Many bright spots were confirmed in the field, suggesting that pressure nodes of the standing wave field are arranged in a lattice pattern.…”
Section: Visualization Of the Ultrasound Field In Watermentioning
confidence: 99%
“…Kudo et al formed a complicated sound field and observed it by an optical technique. 15,16) Recently, an ultrasonic atomizer with a horn has become commercially available. By using a horn, the atomization rate can be expected to increase because the diffusing sound wave can be focused to form the higher sound pressure amplitude at the atomization point.…”
mentioning
confidence: 99%